PROFILE OF KELOID PATIENTS IN SURGICAL WOUNDS: A STUDY AT DEPARTMENT OF PLASTIC AND RECONSTRUCTIVE SURGERY, DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA (2019-2022) - Nurfaiza, Diandra Yasmin; Saputro, Iswinarno Doso; Indramaya, Diah Mira; Aruja Dhar; Saleh Ashafi; Milan Muhammed (Jurnal Rekonstruksi dan Estetik, 2025)
Highlights: Previous keloid surgery mostly caused keloid recurrence. The most common symptom that accompanies keloids in surgical wounds was itching. Surgery and combination therapy were the most used therapy. Abstract: Introduction:   Keloid is an abnormal scar resulting from disruptions in the wound healing process. Clinically, keloids extend beyond the original wound margins and progressively enlarge into dense, firm nodules. They can develop following various forms of trauma, including surgical procedures. Several factors contribute to keloid formation in surgical wounds, such as age, gender, genetics, skin color, hormones, incision location, wound tension, and delayed healing. Methods: This retrospective descriptive study analyzes medical records of patients diagnosed with keloids due to surgical wounds at the Department of Plastic and Reconstructive Surgery, Dr. Soetomo General Academic Hospital, Surabaya, between 2019 and 2022. Results: Among 58 keloid patients, 23 developed keloids following surgery. The most common risk factor was a history of previous keloid surgery. The majority of patients were female, aged 17–25 years, students, and had no family history of keloids. The most frequent keloid location was the chest, with an onset of ≥1 year, a size of <20 cm², and associated itching. Surgical excision and combination therapy were the most commonly used treatment approaches. Conclusion: Previous keloid surgery is the primary risk factor for developing keloids in surgical wounds. Surgery and combination therapy remain the most frequently employed treatment strategies.